L’évolution de la doctrine nucléaire américaine de contreforce - David, Charles-Philippe (Études internationales, 1986)
There has been a tendency lately in the United States to talk about the breakdown of the domestic consensus on the purpose of American nuclear strategy. The Reagan administration policies have been largely responsible for the growing felt need by many to question the doctrine and plans underlining that strategy. Why did the erosion of the strategic consensus take place ? One explanation examined in this paper is that the U.S. government has appeared in its nuclear strategy to emphasize more and more counterforce and limited nuclear war plans as its nuclear weapons policy, and therefore has become increasingly receptive to the idea that atomic bombs can be treated like conventional weapons and thought in ways characteristic of the pronuclear world. The central purpose of this article is to analyze how those two phenomenons - the attractiveness of counterforce and the erosion of the strategic consensus - are related to one another. The evolution of the doctrine of counterforce is assessed through a survey of the literature from 1974 to 1984, and particularly from 1980 with the coming to power of the Reagan administration.